Review on the challenges of hybrid propulsion system in marine transport system - Damian S.E.; Wong L.A.; Shareef H.; Ramachandaramurthy V.K.; Chan C.K.; Moh T.S.Y.; Tiong M.C. (Elsevier Ltd, 2023)
Battery storage; Electric batteries; Electric power supplies to apparatus; Electric power systems; Ship propulsion; Battery energy storage systems; Control strategies; Electrical power; Electrical systems; Fuel efficiency; Hybrid propulsion systems; Marine transport; Optimal sizing; System supply; Transport systems; Ships